2021
DOI: 10.13005/msri/180203
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Applications of Biosynthesized AgNPs: A Short Review (2015-2020)

Abstract: Bacterial resistance to a wide spectrum of antimicrobial medicines has evolved as a major public health concern. Antibiotics are medications that are used to kill microorganisms that could cause serious illness or death. Nanotechnology has exploded as a significant and appealing field of research, with innovative features and functionalities in a variety of fields. Silver is a versatile antibacterial and anticancer medicinal agent in the form of nanoparticles. Silver Nanoparticles (AgNPs) have been implicated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Research indicates that AgNPs are more effective against Grampositive bacteria, such as Staphylococcus aureus, due to the structural peculiarities of Grampositive cell walls, which allow easier penetration of nanoparticles. In contrast, their action against Gram-negative bacteria, like Escherichia coli, Pseudomonas aeruginosa, and Klebsiella pneumoniae, involves complex interactions with outer membrane proteins and the periplasmic space, which may also lead to the disruption of the bacterial membrane integrity [123].…”
Section: Application Of Cannabis-based Agnps Antibacterial Properties...mentioning
confidence: 99%
“…Research indicates that AgNPs are more effective against Grampositive bacteria, such as Staphylococcus aureus, due to the structural peculiarities of Grampositive cell walls, which allow easier penetration of nanoparticles. In contrast, their action against Gram-negative bacteria, like Escherichia coli, Pseudomonas aeruginosa, and Klebsiella pneumoniae, involves complex interactions with outer membrane proteins and the periplasmic space, which may also lead to the disruption of the bacterial membrane integrity [123].…”
Section: Application Of Cannabis-based Agnps Antibacterial Properties...mentioning
confidence: 99%
“…coli was employed in this investigation to examine the bacte ricidal activity of hydrogels encapsulating AgNPs since it's gen eral known that AgNPs have potent antibacterial effects. [54][55][56] E. coli initially cultivated on solid LBagar utilizing silver nan oparticlecontaining hydrogels as the experimental group and pure PEG hydrogels served as the experimental control. After an overnight incubation, it was revealed that a growth inhibi tion halo was only clearly apparent around hydrogel containing AgNPs (see Figure 7b).…”
Section: Antibacterial Effect Of Prepared Hydrogelsmentioning
confidence: 99%
“…Bacterial membranes are largely loaded with negative charges due to the presence of lipopolysaccharide, peptidoglycan, and various groups, including carboxyl, amino, and phosphate groups. 176,177 Electrostatic attraction aids AgNPs adhesion to bacterial membranes when positive charges are present. As a result, adjusting the charge on the surface of AgNPs might help them have a better antibacterial activity.…”
Section: Various Uses Of Agnpsmentioning
confidence: 99%